Understanding the importance of therapeutic alliance during physiotherapy treatment for musculoskeletal pain in children: a scoping review - Joslin, Rhiannon; Allen, Eve; Carter, Bernie (Frontiers in Pain Research, 2024)
IntroductionMusculoskeletal pain affecting children is common. Rehabilitation and treatment effectiveness can be influenced by multiple individual and contextual factors. The need for more rigorous evaluation of physiotherapy treatment for children's pain, identification of the role of specific techniques, and exploration of the influence of the therapeutic alliance is needed. This scoping review of research aimed to examine: (1) What are the perceptions of children, parents, and physiotherapists about the importance of therapeutic alliance during musculoskeletal pain treatment? (2) What are the key characteristics of therapeutic alliance during a child's musculoskeletal pain treatment from the perspectives of children, parents, and physiotherapists? and (3) What are the perceived impacts of therapeutic alliance (positive and negative) during a child's physiotherapy treatment for musculoskeletal pain?MethodsThe scoping review, based on Arksey and O'Malley's framework and reporting was guided by PRISMA-ScR. The search strategy was based on three concept blocks: (1) Study population: Children (<18 years); (2) Medical condition: Any musculoskeletal pain (acute, chronic primary, chronic secondary); (3) Intervention: Qualitative exploration of experience of physiotherapy treatment delivered by a physiotherapist from the perspective of a child, parent, or physiotherapist. The search (no date limit) was conducted in February 2024 across Medline, AMED and CINAHL.ResultsFollowing duplicate removal and assessment of eligibility of the initial 236 articles, nine articles were included; of these, only one specifically aimed to explore therapeutic alliance and it was the only paper to directly mention therapeutic alliance. All nine articles presented the child's experience. One overarching theme “Finding resilience within me through therapeutic alliance” and three main themes: “A trusted guide through the ups and the downs of rehabilitation”; “Having a route map”; and “Take me seriously but make it fun” were identified.DiscussionTherapeutic alliance was considered important by children, parents and physiotherapist and it influenced child and parent perceptions of physiotherapy and overall treatment outcomes. Physiotherapists can foster the children's resilience when experiencing musculoskeletal pain by providing disciplinary expertise, connecting and collaborating with the child by becoming their trusted guide, and co-creating a route map for rehabilitation by helping them to learn about their body, pain and recovery timeline.